Karakteristik dan Status Kesehatan Mental Ibu Postpartum - Eva Sinaga; Naomi Frolinda Jober (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify the relationship between the characteristics of respondents and the mental health status of postpartum mothers in the working area of the Kotaraja Health Center. The research method used is correlational quantitative research with a cross-sectional approach. The results showed that one third of the total postpartum mothers (32.7%) experienced mental health problems, dominated by the group of early adulthood, low education, married status, poor economic status, multiparous, history of standard delivery, and having children of infant age. The most felt symptoms were somatic symptoms (66.5%) and anxiety (56.2%). The most common specific symptoms were frequent headaches (55%), fatigue (57.8%) and difficulty sleeping (41%). As many as 2.4% of respondents had thoughts of ending their life. In conclusion, there is a significant relationship between educational level and economic status with mental health problems of postpartum mothers. Keywords: Anxiety, Depression, Characteristics, Mother's Mental Health, Postpartum